2008
DOI: 10.1071/rd07172
|View full text |Cite
|
Sign up to set email alerts
|

A unique method to produce transgenic embryos in ovine, porcine, feline, bovine and equine species

Abstract: Transgenesis is an essential tool in many biotechnological applications. Intracytoplasmic sperm injection (ICSI)-mediated gene transfer is a powerful technique to obtain transgenic pups; however, most domestic animal embryos do not develop properly after ICSI. An additional step in the protocol, namely assistance by haploid chemical activation, permits the use of ICSI-mediated gene transfer to generate transgenic preimplantation embryos in a wide range of domestic species, including ovine, porcine, feline, equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 63 publications
2
34
0
2
Order By: Relevance
“…Another innovation in SMGT has been the use of ICSI to deliver transgene-containing sperm cells directly into the egg, a process known as 'ICSI-mediated transgenesis' (ICSI-Tr) which was reported for the first time in mice (Perry et al 1999) and later developed in pigs , Pereyra-Bonnet et al 2008, García-Vázquez et al 2009, Wu et al 2009). These techniques (pronuclear injection and ICSI) are considered as passive methods for transgenesis (Shinohara et al 2007), which rely on the repair mechanisms of the host for transgene insertion.…”
Section: Introductionmentioning
confidence: 99%
“…Another innovation in SMGT has been the use of ICSI to deliver transgene-containing sperm cells directly into the egg, a process known as 'ICSI-mediated transgenesis' (ICSI-Tr) which was reported for the first time in mice (Perry et al 1999) and later developed in pigs , Pereyra-Bonnet et al 2008, García-Vázquez et al 2009, Wu et al 2009). These techniques (pronuclear injection and ICSI) are considered as passive methods for transgenesis (Shinohara et al 2007), which rely on the repair mechanisms of the host for transgene insertion.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we were able to successfully collect sperm from collared peccary testis xenografts and, also for the first time, harvest peccary oocytes, which subsequently after standard ICSI procedures (Pereyra-Bonnet et al 2008) resulted in diploid embryos. Using the PCR technique, we observed that twothirds of the four-cell embryos obtained expressed the paternally imprinted gene NNAT (Park et al 2011, Chankitisakul et al 2012.…”
Section: Experimental Groupmentioning
confidence: 80%
“…As the number of obtained viable oocytes was small, ICSI procedure was carried out using spermatozoa only from testis cell suspension xenografts (eight oocytes), and parthenogenetic embryos were also produced as a control (Pereyra-Bonnet et al 2008). Embryo rate was assessed 24 and 48 h after ICSI, and the DNA content of the parthenogenetic and ICSI embryos was evaluated using NanoDrop (ND1000, Thermo Scientific).…”
Section: Oocyte Sampling and In Vitro Maturation And Icsimentioning
confidence: 99%
“…The number of good quality blastocysts produced following ICSI in our experiments approached those produced by normal IVF. Although further work might push the technology further, the number and quality of embryos obtained with our approach could boost the use of ICSI in several fields of reproduction biotechnologies, such as the production of large transgenic animals as disease models [22,23], as well as the replacement/expansion of animals threatened with extinction [10].…”
Section: Discussionmentioning
confidence: 99%